Characteristics and Paradigm of Sufi Tafsīr in ‘Abid al-Jabiri Epistemology Perspective - Wahyudi, Wahyudi; Zaini, Muhammad (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2018)
The result of Sufi’s interaction and the Holy Qur-an passes out with a distinctive style of Sufi’s Tafsir with its Irfan epistemology. Although the validity of the Sufi interpretations are still disputed by Scholars, it has in fact a thorough epistemological structure. As a result of the interpretations of the Qur-an with a peculiar epistemology, the Sufi interpretations also have the distinctive characteristics and paradigms as well.Amongst the characteristics of Sufi’stafsir is the use of Ta'wil method, interpreting the Qur'an based on the essence of Khafiyah within the process of Riyadah and being performed by the Sufism.The Result of Sufi’s Interpretation of the Holy Qur-an is divided into two categories.Firstly; Free Interpretation, meaning the result of the Sufi’s interpretation spread sporadically in numerous kinds of ingenuity and not codified in one book of interpretation.Secondly; the codified Interpretation, is the result of a codified Sufi’s interpretation and even written in an entire book of tafseer.Concurrently, the paradigm built by the Sufi’s tafsir is the existence of the meaning of zahir and batin in the verses of the holy Qur-an. everyone has a level of understanding in accordance with the habitation which he is located.Thus, The Sufi do not recognize the existence of the absolutism in Interpretations.